Acute effects of chocolate milk and a commercial recovery beverage on postexercise recovery indices and endurance cycling performance - Pritchett, K.; Bishop, P.; Pritchett, R.; Green, M.; Katica, C. (Applied Physiology, Nutrition, and Metabolism, 2009)
To maximize training quality, athletes have sought nutritional supplements that optimize recovery. This study compared chocolate milk (CHOC) with a carbohydrate replacement beverage (CRB) as a recovery aid after intense exercise, regarding performance and muscle damage markers in trained cyclists. Ten regional-level cyclists and triathletes (maximal oxygen uptake 55.2 ± 7.2 mL/kg·min) completed a high-intensity intermittent exercise protocol, then 15-18 h later performed a performance trial at 85% of maximal oxygen uptake to exhaustion. Participants consumed 1.0 g carbohydrate/kg.h of a randomly assigned isocaloric beverage (CHOC or CRB) after the first high-intensity intermittent exercise session. The same protocol was repeated 1 week later with the other beverage. A 1-way repeated measures analysis of variance revealed no significant difference (p = 0.91) between trials for time to exhaustion at 85% of maximal oxygen uptake (CHOC 13 ± 10.2 min, CRB 13.5 ± 8.9 min). The change in creatine kinase (CK) was significantly (p < 0.05) greater in the CRB trial than in the CHOC trial (increase CHOC 27.9 ± 134.8 U/L, CRB 211.9 ± 192.5 U/L), with differences not significant for CK levels before the second exercise session (CHOC 394.8 ± 166.1 U/L, CRB 489.1 ± 264.4 U/L) between the 2 trials. These findings indicate no difference between CHOC and this commercial beverage as potential recovery aids for cyclists between intense workouts.